The role of carcinoembryonic antigen-related cell adhesion molecule 1 in cancer - Lisa Götz; Uwe Rueckschloss; Gözde Balk; Verena Pfeiffer; Süleyman Ergün; Florian Kleefeldt; Florian Kleefeldt (Frontiers in Immunology, 2023)
The Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), also known as CD66a, is a member of the immunoglobulin superfamily. CEACAM1 was shown to be a prognostic marker in patients suffering from cancer. In this review, we summarize pre-clinical and clinical evidence linking CEACAM1 to tumorigenicity and cancer progression. Furthermore, we discuss potential CEACAM1-based mechanisms that may affect cancer biology.